Policy Making Under Discontinuous Change: The Situational Normativism Approach - Shakun, Melvin F. (Management Science, 1975)
Policy making under conditions of discontinuous change is discussed in terms of situational normativism, a descriptive-normative approach to policy making systems. Under such conditions, norms and values play a key role in the adaptation of the system. The nature of norms and values within situational normativism is discussed, and implications for system adaptation are explored. Aspects of policy, strategy, planning and system design are considered. A behavioral model for purposeful search and adaptation under discontinuity is presented. At the policy level a referral process is described which allows for change with respect to the set of operational goal variables. This involves referral between operational goals and nonoperational goals (values) and norms. The use of the model in the situational normativism approach to planning under discontinuity is discussed.